Water Repellent Modified Polyester Fabric Based Triboelectric Nanogenerator for Harvesting Human Mechanical Energies - Utchawadee Pharino; Kanyamon Ausaman; Kunyapak Phonimdang; Satana Pongampai; Wanwilai Vittayakorn; Rangson Muanghua; Narin Atiwongsangthong; Thitirat Charoonsuk; Naratip Vittayakorn (Integrated ferroelectrics, 2021)
Wearable triboelectric nanogenerators (TENGs) for converting human mechanical energies into electricity are being investigated widely, because of their potentially diverse applications that come from wearable power supplied to multifunctional self-powered sensing. However, external influences, such as water or high humidity, seriously degrade the electrical output of TENGs. Therefore, a simple method was implemented for fabricating a water repellent fabric-based TENG for harvesting human mechanical energies. Polytetrafluoroethylene (PTFE) or SiO2 modified by trichloro(octadecyl)silane (OTS) were sprayed onto a polyester (PET) fabric surface to increase hydrophobicity. The PTFE and SiO2/OTS coated polyester fabrics exhibited excellent water repellency with a high-water contact angle of ∼144° and ∼153°, respectively. The surface morphology of the coated fabrics showed roughness with a granular structure, which was responsible for air entrapment that prevented water from penetrating the fabric. Furthermore, electrical output of conventional PET fabric-based TENG was found to improve with the deposition of PTFE particles on the fabric surface. By pairing the PTFE coated fabric with aluminum (Al) tape, in order to fabricate TENG, the device generated a maximum voltage of 10.2 V and short-circuit current of 0.20 µA, with a power output of 0.23 μ W/cm2, which is 14 times greater than that of SiO2/OTS coated fabric-based TENG. The process for achieving water repellent fabric is simple, and the coating materials are available. Thus, a water repellent fabric-based TENG is promising for large-scale production of wearable harvesters from power supplied to multifunctional self-powered sensing.
Keywords: Advanced Sensor and Energy Harvesting Materials; Conducting polymers and applications; Tactile and Sensory Interactions